The Classroom as a Storytelling Space Where the Exotic Meets and Greets the Domestic - Szulia, Jagoda; Brits, Karien (Journal of Literary Studies, 2011)
One of Poland's leading universities offers South African studies to Polish students of English. Here, Polish students learn about the South African reality first and foremost in cultural studies and Afrikaans-language acquisition classes. This is not as easy as it might seem at first glance. There are thousands of kilometres, in a literal and figurative sense, of almost completely unknown territory between Poland and South Africa. The distance, however, does not necessarily have to stand in the students' way to successfully and comprehensively study a subject many of them previously deemed to be essentially ·exotic". In order to assure a full understanding of a given culture, one should preferably immerse oneself in it, otherwise it will remain remote and exotic. This article illustrates how to, through experiential learning and teaching, practically bridge the gap between this ·exoticism" and the "domestic", well-known "Polishness" of the learners. This is done within the classroom that becomes the meeting point where two different countries and even more different cultures and languages meet. Opsomming Een van Pole se leidende universiteite bied Suid-Afrikaanse studies vir Poolse studente van Engels aan. Hier leer Poolse studente die Suid-Afrikaanse realiteit ken, veral in kultuurstudies en in taalverwerwingsklasse (Afrikaans). Dit is nie so maklik as wat dit met die eerste oogopslag mag lyk nie. Daar le letterlik en figuurlik duisende kilometer se totaal onbekende terrein tussen Pole en Suid-Afrika. Die afstand hoef egter nie die studente te verhinder om 'n vak wat baie van hulle voorheen as wesenlik "eksoties" beskou het, omvattend en suksesvol te bestudeer nie. Om seker te maak dat jy 'n gegewe kultuur ten voile verstaan, behoort jy verkieslik heeltemal daarin opgeneem te word, andersins sal dit ver en eksoties bly. Hierdie artikel loon aan hoe die gaping tussen hierdie "eksotisme" en die "huishoudelike" die bekende "Poolsheid" van die leerders, deur ervaringsleer en onderrig, oorbrug word. Dit word gedoen binne die klaskamer wat die ontmoetingspunt word waar twee verskillende lande en selfs meer verskillende kulture en tale ontmoet.